Improving lexico-semantic integration with gesture-enriched pictures: A word-learning study using the Picture-Word Interference paradigm. - Kalénine, Solène; Ott, Laurent; Casalis, Séverine (Memory & Cognition, 2025)
This study aimed to evaluate the impact of static gesture cues on word learning and integration. Following embodied theories of language, gesture-enhanced images displaying the object-use gesture should favor learning and integration of object nouns. Sixty-two adult French speakers learned low-familiarity French nouns of manipulable objects (e.g., "étrille" − currycomb) with gesture-enhanced or neutral images during a short learning session. Immediately after, word recognition (lexical decision) and word production (Picture-Word Interference, PWI) tasks were used to evaluate the impact of image type on word learning and lexical integration, respectively. In the PWI, participants had to name a picture of a familiar object (e.g. "brosse" − brush) while ignoring a written distractor word. Words learned with gesture-enhanced or neutral images were used as distractors. Depending on the condition, they could be semantically related ("étrille" − currycomb) or unrelated ("burin" − chisel) to the target object to name. A control condition with unrelated distractor words not involved in learning ("salière" − salt shaker) was also added. Naming latencies in presence of related distractors, compared to unrelated distractors, indicated whether learned lexical representations engaged in competition during production. Lexical decision results did not show any influence of the image condition used during learning on word recognition. Critically, however, PWI results demonstrated that words trained with gesture-enhanced pictures entailed semantic interference effects during naming. Words trained with neutral pictures did not induce semantic interference. Findings highlight the relevance of gesture cues for lexico-semantic integration of object nouns and suggest considering the role of contextual images in vocabulary acquisition.